The Efficiency of Education Expenditure in Portugal - Clements, Benedict (IMF Working Papers; Working Paper ;, 1999)
This paper assesses the efficiency of education expenditure in Portugal and delineates a possible agenda for reform. Portugal's low educational performance has coincided with the highest level of primary and secondary education expenditure to GDP in the Organization for Economic Cooperation and Development (OECD), suggesting considerable inefficiency. Empirical results from the application of a nonparametric technique for production frontier estimation (Free Disposable Hull analysis) support this view. Among the reforms that could be considered to raise educational efficiency are the adoption of a goal-oriented management and incentive system; establishment of minimum student/teacher ratios; and an easing of employment and work rules governing public school teachers.